PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS KOMPUTER MODEL TUTORIAL INERAKTIF UNTUK SMA KELAS XI MATERI PELUANG - Habiburrahman '; Kartini '; Yenita Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to develop mathematics with computer-based learning media model tutorial interactive model for SMA grade XI subject probability. This research and development use development model ADDIE. Development is done through the following steps: (1) analysis; (2) design; (3) development; (4) implementation and evaluation. At the stage of analysis, the researcher conducted a needs analysis included Core Competence (CC) - Basic Competence (BC) analysis, problems of students analysis, and materials analysis. Then, researcher collect materials to design learning media. Learning media that had been developed validated by five validators and revised based on the input from validators. Validation of media appraise aspects of curiculum, learning, display, program. The valid learning media then tested in two stages, the small group test with subjects are five students of class XI MIPA SMA Babussalam Pekanbaru and large group test with subjects are 30 students of class XI MIPA SMA Babussalam Pekanbaru. Based on the data analysis and discussion can be concluded that the mathematics learning media based computer tutorial interactive model for SMA grade XI subject probability are valid, and obtain good responses from students class XI.Keywords: Computer-based Learning Media, Research and Development, Probability